2013
DOI: 10.1111/jcpe.12157
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between metabolic syndrome and diagnoses of periodontal diseases among participants in a large Taiwanese cohort

Abstract: A small but statistically significant association between MetS and the diagnosis of periodontal diseases was found in Taiwanese women and a weaker association in Taiwanese men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 22 publications
(24 reference statements)
6
44
0
Order By: Relevance
“…However, DM patients had high levels of TRG, above normal values (>150 mg/dL), and were positively correlated with two important periodontal parameters, GR and CAL. Our results are in agreement with Tu et al 24 who evaluated associations between lipid parameters and periodontitis and found a positive correlation for TRG and C-reactive protein (CRP). Controversially, Sora et al 25 evaluated the relationship of metabolic syndrome (five cardiovascular risk factors: abdominal obesity, hypertension, reduced HDL, elevated TRG and elevated…”
Section: Immunological Analysissupporting
confidence: 83%
“…However, DM patients had high levels of TRG, above normal values (>150 mg/dL), and were positively correlated with two important periodontal parameters, GR and CAL. Our results are in agreement with Tu et al 24 who evaluated associations between lipid parameters and periodontitis and found a positive correlation for TRG and C-reactive protein (CRP). Controversially, Sora et al 25 evaluated the relationship of metabolic syndrome (five cardiovascular risk factors: abdominal obesity, hypertension, reduced HDL, elevated TRG and elevated…”
Section: Immunological Analysissupporting
confidence: 83%
“…31,32,44 Other variations include the number of teeth and sites on teeth examined. 25-32,39,44-47 A few studies used self-evaluation of the periodontal condition 48,49 or tooth mobility and a non-specified index of gingival inflammation 50 (Tables 1 and 2). …”
Section: Critical Factors Involved In Assessing the Association Bementioning
confidence: 99%
“…67 However, some of these studies identified the exposure (explanatory or independent) and outcome variables 25,30,32,34,36,44-46,48,51 with directionality (Tables 1 and 2). For other studies which did not identify the exposure and outcome variables, 31,33,35,37,38,40,41,44,47,50 we interpreted directionality based on the authors’ description. There are only a few case control studies 30,32,36 and longitudinal studies are available.…”
Section: Critical Factors Involved In Assessing the Association Bementioning
confidence: 99%
“…Also, in patients with diabetes mellitus and periodontal disease, there may be an increase in some inflammatory factors such as IL6 and TNFα that results in dyslipidemia and hypertriglyceridemia (44,45). In one cohort study evaluating the relationship between metabolic syndrome and periodontal disease, Tu et al showed that patients with periodontal disease have higher levels of blood triglycerides (14). In a study conducted by Mointaghavi et al, no significant decrease was observed in serum TG in diabetic patients after periodontal treatment (34).…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory factors may adversely alter blood glucose and lipid metabolism (13). In a large cohort study in Taiwan (from 2003 to 2009), a significant association was observed between metabolic syndrome and diagnosis of periodontal disease (14). According to the findings of some studies, periodontal inflammation is associated with a significant increase in Hemoglobin A1c (HbA1c), Fasting Blood Sugar (FBS) and inflammatory factors in patients with diabetes mellitus (15,16).…”
mentioning
confidence: 99%